ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN MINAHASA - Rattu, Billy Ch. G.; Poputra, Agus T.; Kalalo, Meily Y. B. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Â Â Â Â Â Â Â Â Â Â Â  Own-Source Revenue is a source of regional financial and funding of the government. One of the revenues comes from local tax, and that becomes one of the government of MinahasaRegency is Non Metallic Minerals Tax and Rocks. This research was conducted to determine the level of effectiveness and contributions Non Metallic Minerals Tax and Rocks as a source of revenue Minahasa regency.Non Metallic Minerals Tax and Rocks is tax on the extraction of non metallic minerals and rocks , either from natural sources inside and/or the surface of the earth to be used. The method of research is using qualitative descriptive data types. The research is confined to the calculation of the percentage of effectiveness and contributions obtained from the quantitative data relating to the acceptance of Non Metallic Minerals Tax and Rocks.The results of research suggests that the effectiveness of Non Metallic Minerals TaxÂ  and Rocks in 2012, 2013 and 2014 year is â€œvery effectiveâ€ and effectiveness rate is highest in 2014 which amounted to 159.20 % .Meanwhile , the contribution rate of Non Metallic Minerals Tax and Rocks in the last three years continues to decline so that the criteria included the contribution is â€œvery lessâ€. Tax collection system should be kept under surveillance so that tax revenue of Metallic Minerals Tax and Rocks controlled and remains highly effective .Â Keywords: revenue, non metallic minerals tax and rocks, effectiveness, contributions